Climate Change and Aquatic Animal Disease - International Center for Tropical Agriculture; CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
More than 4.5 billion people get at least 15% of their average per capita intake of animal protein from fish. Fish is therefore a key element in food security and human nutrition. Analysis of future fish supply-demand scenarios suggests that farming of fish and other aquatic products will need to double production by 2030 to meet growing demand. About half of the demand for these foods is now met by aquaculture and Asia accounts for the bulk (90%) of the global aquaculture production of 66 million tones. However, aquaculture operations in the tropics experience higher cumulative mortalities and faster progression of diseases and this could be exacerbated by climate change leading to selection of virulent pathogens that have the potential to spread. This can result in introduction and spread of more virulent pathogens to natural fisheries and aquaculture landscapes, threatening a significant part of the global supply of nutritious animal foods. Understanding the interaction between climate sensitive aquaculture landscapes along with their aquatic hosts and climate sensitive aquatic animal diseases, mapping of potential risks, identification of suitable adaptation/mitigation intervention strategies should be the focus of future research and development, if we are to meet the future seafood demand for 9 billion people by 2050. There is paucity of information as to how aquatic animal disease outbreak dynamics are mediated by climate driven changes and what impact this will have on the future of aquaculture growth in the world, especially in Asia and Africa. This submission was prepared by Chadag Mohan, World Fish Center, Penang, Malaysia, with support from the CGIAR research program on Climate Change, Agriculture and Food Security (CCAFS).